Taxonomic reappraisal of Hynobius tokyoensis, with description of a new species from northeastern Honshu, Japan (Amphibia: Caudata) - Matsui, Masafumi; Misawa, Yasuchika; Yoshikawa, Natsuhiko; Nishikawa, Kanto (Zootaxa, 2022)
Previous phylogenetic studies based on mitochondrial DNA data have consistently suggested that Hynobius tokyoensis consists of two major clades, clade A (northern clade) and clade B (southern clade). In this study, we newly estimated their population genetic structure and phylogenetic relationships by nuclear SNPs, and the results suggested heterospecific relationships of the two mitochondrial clades, without present hybridization in between. They were also recognized as morphologically different. The type locality of H. tokyoensis is in Tokyo Prefecture, and therefore clade B corresponds to H. tokyoensis sensu stricto, leaving clade A without available scientific name. We, thus, describe the clade A from northeastern Kanto to southern Tohoku as a new species Hynobius sengokui. The new species is distinguished from H. tokyoensis by its relatively longer axilla-groin distance, shorter trunk, and deeper vomerine teeth series, and is estimated to have diverged from it during the late Pliocene.